Design concept for green public space in kampong - Widharto, Sukmo D.; Muchlis, Nurfahmi; Laksono, Sigit H.; Setijanti, Purwanita (Journal of Architecture and Urbanism, 2015)
The lack of environmentally friendly development in major city has made the public space in kampongs (or kampung) neglected. The need of a green community space to interact is increasingly scarce. The remaining areas that can be used as an outdoor space are alleys and pathways inside kampong. Public space should then be adaptive in order to meet the demands in a diverse society, thus emerged a design concept of adaptive public space using the capabilities of bamboo to deliver adaptive spaces with a limited range of conditions in its design, construction and usability. Bamboo has been frequently used by the people because of its sustainable characteristic. The method used in this study is the case study method. Qualitative data were collected through observations and interviews resulted in the analysis of existing conditions then formulized as a design criteria. Design method uses the concept of programming which is to formulate the mission, goals and performance requirements to create a concept. The drawn conclusion is that the alleys inside the kampong can be used as a public space by applying adaptive design principles. The use of bamboo in design is an appropriate solution based on its construction and material properties.